Conservation and Value Added of Manuscript Wrap Based on Creative Economy - Somsri, Chaiwat; Kittiporn Sangkadis; Jomkwan Wiangngern; Nutchanard Chawprayna; Kanniga Sawetpawit; Paramaporn Saengkaensan (Indonesian Journal of Business Analytics, 2025)
The objectives of this research were preserving the identity of local cultural heritage through the study of Manuscript Wrap and enhance the value of this cloth product, The study involved a sample of 400 local residents and tourists in Long District, Phrae Province, selected through simple random sampling. The research instrument was a product market survey adapted from the 4P marketing mix, and data were analyzed using descriptive statistics, including percentages, means, and standard deviations. The results showed that a body of knowledge regarding Manuscript Wrap was developed and a distinctive product pattern that reflects Phrae Province's identity was produced, were created. Furthermore, while the sample generally lacked knowledge about the specifics of Manuscript Wrap there was significant interest in supporting local products, particularly for daily use and as gifts. Overall satisfaction with the product market test was high, with a mean score of 3.95 and a standard deviation of 0.81. Ranking the satisfaction scores revealed that support for sales ranked first (mean = 4.06), followed by satisfaction with price (mean = 4.01), product (mean = 3.93), and place of distribution (mean = 3.83). Notably, integrating the product’s features with local cultural identity and religious beliefs significantly enhanced the value and appeal of Manuscript Wrap